Documentary, linguistic analysis and semantic “Relationship OF THE tirano Aguirre of Gutierre de la Peña” in New Segovia of Barquisimeto 1562 (Ágora de Heterodoxias, 2015)
The present essay is located within the discipline of historical lexicography. It seeks to contribute with knowledge of linguistic and semantic aspects through the lexicon registry and grafematics particularities and contrastive in an original document from the year 1561. Its origin, validity, meaning and other aspects that contribute to the understanding of the language of that moment in particular it is stated.
Keywords: historical lexicography; contrastividad; semantic fields; military actions